UPAYA PENINGKATAN PRODUKTIFITAS KEBUN KOPI RAKYAT SYSTEM AGROFORESTRY DI KELURAHAN UJAN MAS ATAS, KABUPATEN KEPAHIANG, PROVINSI BENGKULU - Hery Suhartoyo; Helfi Eka Saputra; Umi Salamah (Prosiding Seminar Nasional Pengabdian Kepada Masyarakat, 2020)
Abstract Coffee plantation within community forest (HKm) requires the use of an agroforestry system, but knowledge of the concept and its implementation in the field, is still lacking. The use of shade trees in coffee plantations is known to be beneficial for the long-term sustainability of coffee production. Recent result of coffee harvests are still low due to minimal intensification methods and maintenance e.g. in returning of soil nutrients into the agroforestry system. This community service program is carried out to, first, provide an understanding of the importance of shade trees within coffee plantations in the Agroforestry system, second, restore and increase soil nutrients by making compost from coffee husks. And third, introduce red-picking fruit harvest to increase the value of the community's coffee bean. The results of the activity showed better understanding in the arrangement of shade trees and increased skills in composting from coffee husks. The increase in crop yields is still in the implementation stage by using self-made compost which is sown on coffee plantations. The sustainability of this program can be achieved by involving young people in forest farmer groups and the coffee composting business can provide income, in addition to being used alone in their coffee plantation. With the addition of coffee husk compost, it is believed that it will increase coffee yields in the future and with changes in the red-picking harvest pattern, the price of coffee bean will be higher. Abstrak Penanaman kopi rakyat di areal Hutan kemasyarakatan (HKm) mensyaratkan penggunaan sistem Agroforestry, namun pengetahuan tentang konsep dan implementasi Agroforestry di lapangan masih sangat minim. Penggunaan pohon naungan dalam kebun kopi telah diketahui manfaatnya untuk keberlanjutan produksi kopi dalam jangka panjang. Hasil panen kopi yang dihasilkan masih rendah sengan minimnya intensifikasi perawatan dan pengembalian hara tanah ke dalam system Agroferestry. Program pengabdian ini dilaksanakan untuk 1. Memberikan pemahaman tentang pentingnya pohon naungan dalam kebun kopi rakyat system Agroforestry, 2. Mengembalikan dan meningkatkan unsur hara tanah dengan pembuatan kompos dari kulit kopi. 3. Memberikan wawasan pola panen petik merah untuk peningkatan nilai panen kopi masyarakat. Hasil kegiatan menunjukkan pemahanman yang lebih baik dalam hal pengaturan pohon naungan dan meningkatnya ketrampilan dalam pembuatan kompos dari kulit kopi. Peningkatan hasil panen masih dalam tahap implementasi/pemakaiana kompos hasil pembuatan sendiri yang ditabur di lahan kebun kopi. Keberlanjutan program ini dapat dicapai dengan pelibatan kaum muda di kelompok tani hutan dan usaha pembuatan kompos kopi dapat memberikan pendapatan, selain dipakai sendiri di kebun kopinya. Dengan penambahan kompos kulit kopi dipercaya akan meningkatkan hasil panen kopi di masa yang akan datang dan dengan adanya perubahan pola panen petik merah membuat harga kopi yang dihasilkan akan lebih tinggi.